The Future Perspective of School Flood Disaster Education in Semarang - Ferani Mulianingsih; Erni Suharini; Eko Handoyo; Arif Purnomo (International Conference on Science, Education, and Technology, 2023)
Data from BPBD in 2022, there are 142 junior high schools affected by the flood disaster. One of the concerns of disaster management is that people are reluctant to start pre-disaster measures at the individual level. Disaster education taught in schools, offers the most important answers for disaster mitigation. This study aims to identify factors that increase student awareness for flood disaster reduction. This study is based on a survey in five junior high schools in Semarang. Different levels of awareness have been defined to identify factors for effective education at each level. The results of the study show that disaster education in schools can currently increase the perspective of flood disaster risk, but students do not yet know the importance of pre-flood disaster and take concrete actions to reduce flood risk. Future disaster education in schools can be an active learning for students. Community involvement is the most important factor in disaster education in schools.